Pengembangan Media Komik Berbasis Kearifan Lokal dalam Pembelajaran Tematik Terpadu - Nur Ngazizah; Rosita Rahmawati; Dwi Lestari Oktaviani (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
The use of comics media as a support for learning activities with the background of learning activities that are less attractive to students so that students get bored quickly in the learning process. The purpose of this study is to develop comics as a learning medium, to determine the feasibility, to test the effectiveness of comics as teaching materials and to determine students' interest in using comics media. The subjects in this study were several teachers and students at SD Purworejo and the method of data collection was by the teachers and students filling out the questionnaire that had been given by the researcher. The results of the study indicate that the need for comics media is used as a learning medium.